2010
DOI: 10.1007/s11664-010-1146-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Catastrophic Optical Mirror Damage in High-Power Diode Lasers

Abstract: We image catastrophic optical mirror damage (COMD) in red-and infraredemitting high-power broad-area diode lasers by combining highly COMDselective thermography, near-field imaging, scanning electron microscopy, and cathodoluminescence. All techniques exhibit strong correlations in terms of COMD location and strength and allow for an unambiguous decision about COMD occurrence. In particular, temperatures en route to and during COMD are measured, and the concept of a critical facet temperature that induces ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Moreover, the thermal runaway in COD creates a 'thermal flash' of Planck's radiation which can be detected by thermography. Although this 'thermal flash' of infrared emission does not allow for any direct T facet -measurement, it unambiguously indicates the onset of the thermal runaway and can be used for COD analysis [24,74,87,151,152]. This approach will be discussed in chapter 4.…”
Section: Further Approaches For Facet Temperature Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the thermal runaway in COD creates a 'thermal flash' of Planck's radiation which can be detected by thermography. Although this 'thermal flash' of infrared emission does not allow for any direct T facet -measurement, it unambiguously indicates the onset of the thermal runaway and can be used for COD analysis [24,74,87,151,152]. This approach will be discussed in chapter 4.…”
Section: Further Approaches For Facet Temperature Analysismentioning
confidence: 99%
“…COD in 650 nm emitting BA lasers with a stripe width of 100 μm has been investigated by Ziegler et al [74,151] in L I-type experiments. Figures 8a-c show thermal images 2.3 ms before, directly at, and 2.3 ms after the onset of the thermal runaway.…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…This equation was solved using the method of Green's functions and, after imposing the necessary boundary and initial conditions, the time-dependent temperature profiles for the laser were computed. A comparison between the results for catastrophic degradation times vs. amplitude of the pulses as derived from the models by Henry et al [31], Kappeler et al [34] and Nakwaski [35], is shown in Figure 7.…”
Section: Physical Models For Codmentioning
confidence: 98%
“…In the narrow stripe index-guided laser diode design, the fundamental waveguide mode is used and its mode size is limited to be around several microns. However, high power operation requires a broad-area, large emitting aperture to overcome catastrophic optical damage (COD) and help with heat dissipation 4 , 5 . A commercial available high-power broad-area laser diode usually has a width of ~100 μm .…”
Section: Introductionmentioning
confidence: 99%